Implikasi Pilihan Metode Konversi Suara Terhadap Proporsionalitas Perolehan Kursi Dalam Pemilihan Umum Anggota Dewan Perwakilan Rakyat - Hantoro, Bimo Fajar (UI Scholars Hub, 2021)
Choice of vote conversion method, as an element of the general election system, has implications for the degree of proportionality. The degree of proportionality in question is divided into two elements, namely between the percentage of seats acquired and the fairness to large and small parties. The author here is interested in measuring the degree of proportionality generated by each of the vote conversion methods. The author then performs a simulation to measure these two elements from two families of vote conversion methods, namely the Quota method and the Divisor method. The simulation results show that in terms of proportionality of votes with seats, the Hare Quota method is the most proportional, followed jointly by the Droop Quota and the Sainte-Laguë Divisor in the second position, the Imperiali Quota and the Modified Sainte-Laguë Divisor in the third position, and D'Hondt Divisor as the one with the lowest proportionality.